Ontosonographic Maps: Toward a Theoretization of Soundscape Forms in the Anthropocene Epoch - Filipović, Andreja (Etnoantropološki problemi / Issues in Ethnology and Anthropology, 2021)
This paper deals with the ways in which it is possible to conceptualize and map forms of soundscape in the epoch of the Anthropocene. After humans became a geological force, which is a role that used to be reserved for the planet itself, one can pose the question of how to understand this new condition through sound, as well as of the ways in which (re)production of the Anthropocene is heard and performed through sound. With the usage of the terms world, globe, Earth and the planet, a certain understanding of the human environment, current state of affairs, but also of the past and the future is projected. To these terms I connect different ways of production and reception of sound (bio-melo-technology, bio-aural-technology, zoe-aural-technology), and describe their mutual relations through the concepts of biosound, zoesound, necrosound, geosound, and petrosound. I produce this typology on the basis of ontosonographic methodology, and apply it to particular case studies such as popular music (k.d. lang, Lesbian on Ecstasy, My Bloody Valentine, black metal, noise), sounds insects make, and the noise produced by urban traffic. With the help of ontosonographic methodology I map forms of being and becoming through sound and as sound, which makes ontosonography a key concept for understanding the soundscape forms of the Anthropocene. Of decisive importance for understanding the Anthrpocene soundscape is the relation between biosound and geosound, which is produced through petrocultures understood as a multiplicity of practices of extraction and exploitation of fossil fuels. The dominant form of soundscape in the epoch of the Anthropocene is the petrosound. Also, a new way for understanding fossil fuels appears as a possibility, a way that is grounded in a non-binary way of thinking beyond the difference between Life and Non-Life. It remains as a task for further research whether to approach this petrocultural non-binarity through radical or absolute immanence or, perhaps, some other set of concepts more appropriate for the Anthropocene.